236 Factors Influencing Clearance of Pregnancy-associated Glycoproteins in Postpartum Beef Cattle. (8th October 2021) - Kline, Adalaide C; Walker, Julie; Andrews, Taylor; Zoca, Saulo Menegatti; Epperson, Kaitlin M; Quail, Lacey; Rich, Jerica J; Perry, George A; Rhoades, Jim R
Abstract: Blood pregnancy tests can determine pregnancy status in cattle; however, pregnancy-associated glycoproteins (PAGs) have a long half-life (80 to 100 d). If tested too soon after calving, false positive readings can occur due to elevated concentrations from the previous pregnancy. This study's objective was to determine factors that impact clearance of PAGs in postpartum beef females. Blood samples were collected from postpartum Angus and Angus-cross females (primiparous n = 46 and multiparous n = 58); once a week for up to 14 weeks after calving (range of first to last sample 1–7 to 98–105 days postpartum; dpp). Serum was tested in duplicate using the IDEXX Alertys Pregnancy Test. Data were analyzed as a repeated measure using the MIXED procedure of SAS (9.4) with parity, calf sex (sex), days postpartum, and all interactions in the model. Data were analyzed using the REG procedure in SAS. There was a significant effect of dpp (P < 0.01) on PAG concentrations; however, PAG concentrations were not influenced by parity (P = 0.24), sex (P = 0.49), parity by dpp (P = 0.12), parity by sex (P = 0.65), sex by dpp (P = 0.37), or parity by sex by dpp (P = 0.99). Concentrations of PAGs rapidly decreased from d 0 to 50 postpartum and then continued to gradually decrease to d 100. Days postpartum accounted for 67.53% of the variation in PAG concentrations. Prior to 50 dpp, PAG concentrations were sufficiently elevated which resulted in false positive readings (S – N ≥ 0.3). In summary, concentrations of PAGs remained elevated after calving, but the clearance of PAGs were not impacted by parity or sex of the calf. Clearance of PAGs were significantly influenced by days postpartum. Additionally, using a blood pregnancy test prior to d 50 postpartum would increase the likelihood of false positive readings due to residual PAG concentrations from the previous pregnancy.